(untitled) (Medicine Today, 2015)
Rheumatic mitral valvular heart disease is common in developing countries although its incidence is decreasing in western countries. Closed mitral commissurotomy (CMC) was the first effective intervention in valvular heart disease which provides excellent long-term hemodynamic and clinical improvement. In this study we are presenting a successful mitral valve replacement in reoperation of a case who had CMC operation 10 years ago. It shows when symptomatic deterioration occurs late after CMC, MVR restores clinical and hemodynamic improvement in many patients. Medicine Today 2014 Vol.26(2): 111-113